Childhood socioeconomic status and adulthood dietary diversity among Indonesian adults - Isaura, Emyr Reisha; Chen, Yang-Ching; Yang, Shwu-Huey (Frontiers in Nutrition, 2022)
Food insecurity problems still exist among people in low-to-middle-income countries. The long-term disadvantages of socioeconomic status may contribute to chronic food insecurity. However, whether childhood socioeconomic status factors are related to food insecurity in adulthood remains unclear. Thus, this study aimed to test the association between childhood socioeconomic status factors and one of the proxies for adulthood food security, dietary diversity. This study used the 2014 RAND Indonesia Family Life Survey dataset with 22,559 adult participants as study samples. Childhood socioeconomic status factors consisted of 16 questions about participants’ condition when they were aged 12 years. Adult dietary diversity was assessed using the United Nations World Food Programme's food consumption score. Linear regression models were used to analyze the association between variables. This study found that the number of owned books (β coef.: 3.713-7.846, p< 0.001), the use of safe drinking-water sources (β coef.: 0.707-5.447, p<0.001-0.009), and standard toilets (β coef.: 1.263-4.955, p<0.001-0.002), parents with alcohol consumption habits (β coef.: 2.983, p=0.044) or the combination with smoking habits (β coef.: 1.878, p<0.001), self-employed with the permanent worker (β coef.: 2.904, p=0.001), still married biological parents (β coef.: 1.379, p<0.001), the number of rooms (β coef.: 0.968, p<0.001), people (β coef.: 0.231, p<0.001), and younger siblings (β coef.: 0.209-0.368, p<0.001-0.039) in the same house, were positively and significantly associated with the outcome variable, respectively. Further, in the order of childhood socioeconomic status factors, self-employment without permanent workers and casual work types (β coef.: -9.661 to -2.094, p<0.001-0.001), houses with electricity facilities (β coef.: -4.007, p<0.001), and parents with smoking habits (β coef.: -0.578, p=0.006) were negatively and significantly associated with the food security proxy. In conclusion, childhood and early socioeconomic disadvantage is related to adult food security status and may lead to poor health.